Respostas

2013-05-14T19:36:51-03:00

X - Y = 1/5

3X - 2Y = 6/5

_______________

5X - 5Y = 1             (x-2)

15X - 10Y = 6

_______________

-10X + 10Y = -2

15X - 10Y = 6

_______________

-10X + 10Y = -2

5X = 6

X = 6/5

 

 

6/5 - Y = 1/5

Y = 1

 

4 5 4
2013-05-14T21:07:13-03:00

 

 

      3x - 2y  = 6/5

        x -  y    = 1/2   ( I )

 

 

     Mulriplicando o 2º termo por  -2, vem

 

       3x - 2 y  = 6/5

      -2 x + 2 y = -1

___________________

       x         =    1/5

 

  Sibstituindo  em ( I ), vem:

 

 

        1/5  - y  = 1/2

 

 

         - y  =   1/2 - 1/5

 

           y =  - 3/10

 

 

 Resposta :    x =   1/5  e    y = 3/10